Inoculation of Transgenic Resistant Potato by Phytophthora infestans Affects Host Plant Choice of a Generalist Moth. - Kibrom B Abreha; Erik Alexandersson; Jack H Vossen; Peter Anderson; Erik Andreasson (PLoS ONE, 2015)
Pathogen attack and the plant's response to this attack affect herbivore oviposition preference and larval performance. Introduction of major resistance genes against Phytophthora infestans (Rpi-genes), the cause of the devastating late blight disease, from wild Solanum species into potato changes the plant-pathogen interaction dynamics completely, but little is known about the effects on non-target organisms. Thus, we examined the effect of P. infestans itself and introduction of an Rpi-gene into the crop on host plant preference of the generalist insect herbivore, Spodoptera littoralis (Lepidoptera: Noctuidae). In two choice bioassays, S. littoralis preferred to oviposit on P. infestans-inoculated plants of both the susceptible potato (cv. Desiree) and an isogenic resistant clone (A01-22: cv. Desiree transformed with Rpi-blb1), when compared to uninoculated plants of the same genotype. Both cv. Desiree and clone A01-22 were equally preferred for oviposition by S. littoralis when uninoculated plants were used, while cv. Desiree received more eggs compared to the resistant clone when both were inoculated with the pathogen. No significant difference in larval and pupal weight was found between S. littoralis larvae reared on leaves of the susceptible potato plants inoculated or uninoculated with P. infestans. Thus, the herbivore's host plant preference in this system was not directly associated with larval performance. The results indicate that the Rpi-blb1 based resistance in itself does not influence insect behavior, but that herbivore oviposition preference is affected by a change in the plant-microbe interaction.